PENJAMINAN DAN PENGENDALIAN MUTU PENDIDIKAN ISLAM - ., Kasmawati (Universitas Islam Negeri Alauddin Makassar, 2020)
Education is considered as the most valuable investment in the form of an increase in the quality of human resources to measure the extent of the community's education. The higher education the community has, the more the nation will advance. The quality of education is not only seen from the magnitude of the educational facilities it has, but the extent to which the autput (graduate) of an education can develop as a complete human being as the stages of education are